2004
DOI: 10.1002/for.921
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in the link between the yield spread and industrial production: threshold effects and forecasting

Abstract: We analyze the nonlinear behavior of the information content in the spread for future real economic activity. The spread linearly predicts one year ahead real growth in nine industrial production sectors of the US and four of the UK over the last forty years. However, recent investigations on the spread-real activity relation have questioned both its linear nature and its time-invariant framework. Our, in-sample, empirical evidence suggests that the spread real activity relationship exhibits asymmetries that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Gertler and Cara (1999) and Moody & Taylor (2004) found that the yield spread is significant predicting indicator for real economic activity for the United States. Paya, Venetis, and Peel (2004) suggested that the yield spread is one of the most important forecasting Kurihara /International Journal of Finance & Banking Studies Vol 3, No 2, 2014ISSN: 2147 predictors of future output changes. Also, Paya et al found that the yield spread outperforms other predicting indicators for outputs such as money, stock prices, and interest rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gertler and Cara (1999) and Moody & Taylor (2004) found that the yield spread is significant predicting indicator for real economic activity for the United States. Paya, Venetis, and Peel (2004) suggested that the yield spread is one of the most important forecasting Kurihara /International Journal of Finance & Banking Studies Vol 3, No 2, 2014ISSN: 2147 predictors of future output changes. Also, Paya et al found that the yield spread outperforms other predicting indicators for outputs such as money, stock prices, and interest rates.…”
Section: Literature Reviewmentioning
confidence: 99%